Nanotechnology in Eco-Efficient Construction : Materials, Processes and Applications - Torgal, Fernando Pacheco, editor 544911; Diamanti, Maria Vittoria, editor 649032; Nazari, Ali, editor 649033; Granqvist, Claes Goran, editor 649034; Pruna, Alina, editor 649035; Amirkhanian, Serji N., editor 213178; ScienceDirect (Online service) 7722 (Kidlington : Woodhead Publishing, 2019)
Covering the latest technologies, Nanotechnology in eco-efficient construction provides an authoritative guide to the role of nanotechnology in the development of eco-efficient construction materials and sustainable construction. The book contains a special focus on applications concerning concrete and cement, as nanotechnology is driving significant development in concrete technologies. The new edition has 14 new chapters, including 3 new parts: Mortars and concrete related applications; Applications for pavements and other structural materials; and Toxicity, safety handling and environmental impacts. Civil engineers requiring an understanding of eco-efficient construction materials, as well as researchers and architects within any field of nanotechnology, eco-efficient materials or the construction industry will find this updated reference to be highly valuable.